POLA KOMUNIKASI ANTAR UMAT BERAGAMA MASYARAKAT DESA SINDANG JAYA, REJANG LEBONG, BENGKULU - Warsah, Idi; Avisa, Amelia; Anrial, Anrial (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This study aimed at finding out a depiction of the communication pattern among religious people in the Sindang Jaya community, Rejang Lebong Regency, Bengkulu Province. This study used a qualitative approach, and the data collection techniques were observation and interviews. After the data were collected, the analysis was carried out with the stages of reduction, presentation, and drawing conclusion. This study drew the conclusion that First, the pattern of communication set by the people of Sindang Jaya Village was based on mutual respect among religions. Second, there were three forms of tolerance given by the people of Sindang Jaya Village, namely cooperation, religious freedom, and appreciation for the religious activities of other religions. Third, the strategy carried out to avoid conflicts was that both religious leaders, village officials, and the community in general always became fair, respected each other, had kinship relations, discussed every problem, helped each other, and cooperated with one another.